(untitled) (Research, Society and Development, 2025)
Objective: To identify the main health issues affecting healthcare workers, as well as the proposed coping strategies. Methodology: This is an integrative literature review. The article search was conducted in the LILACS, BDENF, SciELO, and PubMed databases, using the descriptors "occupational nursing," "prevention," and "occupational diseases," combined with the Boolean operators "AND" and "OR." After applying inclusion and exclusion criteria, 24 original articles published between 2013 and 2024 were selected and categorized as “A” level evidence according to the Critical Appraisal Skills Programme (CASP) tool. Results: The findings reveal a high prevalence of occupational diseases related to physical overload, exhausting work hours, poor ergonomic practices, stress, and low adherence to norms, protocols, and preventive measures. Among the most frequently reported coping strategies were the implementation of mental health programs, psychological support, promotion of physical activities, and the institutionalization of organizational policies. Final considerations: Occupational nursing plays a strategic role in workplace health surveillance and promotion. Its practice, grounded in humanized approaches such as active listening, risk prevention, and the coordination of protective and educational measures, is essential to achieving a better quality of life in the work environment.